1993
DOI: 10.1523/jneurosci.13-01-00087.1993
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in the frequency representation of primary auditory cortex following discrimination training in adult owl monkeys

Abstract: Previous studies have shown that the tonotopic organization of primary auditory cortex is altered subsequent to restricted cochlear lesions (Robertson and Irvine, 1989) and that the topographic reorganization of the primary somatosensory cortex is correlated with changes in the perceptual acuity of the animal (Recanzone et al., 1992a-d). Here we report an increase in the cortical area of representation of a restricted frequency range in primary auditory cortex of adult owl monkeys that is correlated with the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

53
749
5
13

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,130 publications
(820 citation statements)
references
References 51 publications
(66 reference statements)
53
749
5
13
Order By: Relevance
“…Discrimination thresholds for shifts in the spectral envelope improved steadily over the course of the behavioral training, similar to other auditory discrimination tasks (e.g., Prosen et al;Recanzone et al, 1993;Polley et al, 2006). Analysis of the hit rate and false-alarm rate early and late in training support the conclusion that the observed improvements in discrimination reflect changes in perceptual capacity and not changes in response criterion.…”
Section: Psychophysics Of Ripple Spectrasupporting
confidence: 67%
See 2 more Smart Citations
“…Discrimination thresholds for shifts in the spectral envelope improved steadily over the course of the behavioral training, similar to other auditory discrimination tasks (e.g., Prosen et al;Recanzone et al, 1993;Polley et al, 2006). Analysis of the hit rate and false-alarm rate early and late in training support the conclusion that the observed improvements in discrimination reflect changes in perceptual capacity and not changes in response criterion.…”
Section: Psychophysics Of Ripple Spectrasupporting
confidence: 67%
“…In this way, the spatial resolution of both the signal and the receiver might be improved. The results of this study and others that have observed training-induced refinement of spectral receptive field bandwidth (Recanzone et al, 1993;Witte et al, 2005) might represent initial progress towards this goal.…”
Section: Cortical Plasticity and Perceptual Learningmentioning
confidence: 53%
See 1 more Smart Citation
“…Furthermore, neurons in auditory cortex alter their response properties subsequent to changes in stimulus pairings involved in learning and attention paradigms (e.g., Recanzone et al, 1993;Kilgard et al, 2007;Weinberger, 2007;Zatorre, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, unilateral sound deprivation in adolescent ferrets has been shown to lead to subcortical changes (Moore, 1993), whereas frequency discrimination training in monkeys has been shown to produce alterations in the auditory cortex associated with changes in discrimination ability (Recanzone et al, 1993). When humans have been trained to discriminate speech sounds, changes in preattentive auditory neurophysiologic responses have been linked to perceptual changes (Kraus et al, 1995;Tremblay et al, 1997Tremblay et al, , 1998.…”
Section: Introductionmentioning
confidence: 99%